(3GdehGgH GdbOhSjI aj GdefGbH GdSfhSjIs - (3CHh YHO Gddg eMeO Hf EHQGgje Hf YeQ Hf Ydj GdedGdj, GdedGdj,J (B897 (3g` s ((3CMeO Hf jMji Hf YjSi Hf GHQGgje Hf YjSi s)
(3ChdgG (B:s
(3Chd GdehLhO HgG bhdg (B: (3hGdeY eY Pdc HTF ef ahGFOg heG SeYJ efg ef egeGJ GdeSGFd GdJi CTcdJ Ydi cKjQ ef GdYdeGA GdCYjGf ai gPG GdReGf s
(3BNQgG (B:s
(3hQKGg HYV GdCNHGQ hQKGg GdSjO Gdabjg CHh YHO Gddg eMeO GHf CHj GdHQcGJ Hf CHj jMji Hf CHj GdHQcGJ hBNQ OYhGfG Cf GdMeO ddg GfJgi HMeO s
(3HgG BKGQ JbWjY hWeSs
(3ai GdeYgO fSNJGf BNQjGf HQbe (B2103 (3, (B2104 (3JGQjN s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B301s
Keywords: (3GdJGQjNs